How physical exercise influences academic burnout among Chinese “Double Non” college students: the chain mediation role of mobile phone addiction and learning engagement - Jin, Chao; Fan, Chunhong; Niu, Jinpeng (Frontiers in Psychology, 2024)
Background With mental anxiety caused by the COVID-19 pandemic, the trend of “lying down” has become increasingly prevalent among Chinese college students such as not thinking ahead, decadent abandonment, and being weak daily. Particularly, Chinese “Double Non” college students are more likely to face academic burnout (AB) due to lower school satisfaction and after-degree employment ratio, in comparison to “Double First-Class” college students. Objectives In view of this, the present study examined the structural relationships of physical exercise (PE), mobile phone addiction (MPA), learning engagement (LE), and AB among Chinese “Double Non” college students, aiming at exploring corresponding mechanism to provide supportive guidance for alleviating potential AB. Methods This study adopted a cross-sectional survey approach among the sample of “Double Non” college students in China. We recruited 930 participants (272 men and 658 women) in the second half of the 2022–2023 academic year, all of whom completed questionnaires involving Physical Exercise Rating Scale, Mobile Phone Dependence Index Scale, Utrecht Work Engagement Scale-Student, and Maslach Burnout Inventory-Student Survey. A series of statistical analyses, including descriptive statistics, bivariate correlations, and direct and indirect effects among study variables, were proceeded based on the collected data. Results The results showed that PE can not only directly and negatively influence AB, but also indirectly and negatively influence AB through the mediation of MPA as well as the chain mediation of both MPA and LE. While PE had no significantly indirect effect on AB via LE. Discussion Physical exercise was proved to be an effective way to reduce MPA and then enhance LE, consequently leading to decreased AB in Chinese “Double Non” college students. The findings were discussed in light of related research, and implications and future directions were put forward for application in potential theoretical research and educational practice.